Analisis Strategi Pengembangan Obyek Wisata Pabangbon di Kabupaten Bogor - Riani Prihatini Ishak; Prabowo Eko Julianto (Tourism Scientific Journal, 2020)
Tourism Development is a tourist attraction that will determine the level of income in an area, and all this is shown to give satisfaction to tourists. This research was conducted to determine the development of tourism to visitor satisfaction on Pabangbon Panorama tours. The purpose of this study was to examine the influence of the development of tourism with visitor satisfaction of Pabangbon Panorama Tourism. the research used in this study is visitors who visit Panorama Pabangbon Tourism this research form uses qualitative research. This type of research is qualitative research. Respondents used in this study were visitors who came to Bogor Pabangbon Leuwiliang Panorama tour as many as 60 visitors who came to the tourist attractions. Collecting data in the form of questionnaires in the form of interviews used to see the influence of the development of Pabangbon Tourism. Data analysis used in this study is a graph of the results of interviews that have been obtained and Microsoft Excel computer programs. The results of this study conclude that tourism development chart data at Pabangbon Panorama.